Legal Awareness Socialization in Using Internet in Paulan Village Karanganyar - budiono, arief; Wardiono, kelik; Chandra, Rizky Aditya; Zuhdi, Syaifuddin; Yuspin, Wardah; Farid, Achmad Miftah (Fakultas Hukum Universitas Semarang, 2024)
Indonesia is currently experiencing a very rapid technological advancement. Apart from conducting buying and selling transactions through the internet/digital media, people can also conduct businesses. Then, in this community service program, the authors discussed how to respond to this technological advancement. This is because, in this current millennial era, there is a risk for cyber-crimes and cyberbullying that is currently rampant in every existing social media to obtain money. The target of this socialization is the youth of the Paulan Village Karang Taruna (Youth Organization), Colomadu Regency, Karanganyar Regency, Central Java, Indonesia where almost all of them utilize the Internet in daily life. This community service utilized the descriptive method. The authors employed the legal counselling method as a method of analysis. This legal socialization activity was carried out through lectures, dialogs, discussions, as well as problem resolution related to legal awareness in utilizing the internet and social media with the theme “The Importance of Legal Awareness in Utilizing the Internet and Social Media”. Through this method, participants obtained materials on how to be wise in utilizing social media and the Internet. They are also trained to resolve cyber-crime-related legal issues. After participating in this event, it can be seen that the target of this socialization had a better understanding and knowledge on the Law on Electronic Information and Transaction. Apart from that, they also showed better attitudes in utilizing social media. Socialization should routinely be organized with different materials, while still discussing the importance of utilizing social media